Proceedings of the 2017 ACM on Asia Conference on Computer and Communications Security 2017
DOI: 10.1145/3052973.3053023
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hosting Providers in Fighting Command and Control Infrastructure of Financial Malware

Abstract: A variety of botnets are used in attacks on financial services. Banks and security firms invest a lot of effort in detecting and combating malware-assisted takeover of customer accounts. A critical resource of these botnets is their command-and-control (C&C) infrastructure. Attackers rent or compromise servers to operate their C&C infrastructure. Hosting providers routinely take down C&C servers, but the effectiveness of this mitigation strategy depends on understanding how attackers select the hosting provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Next, we move the level of analysis from individual domains to providers. In areas beyond shared hosting, researchers have repeatedly found that the intermediaries can play a key role in improving security [11,24,26,33,43,44,48,52].…”
Section: Related Workmentioning
confidence: 99%
“…Next, we move the level of analysis from individual domains to providers. In areas beyond shared hosting, researchers have repeatedly found that the intermediaries can play a key role in improving security [11,24,26,33,43,44,48,52].…”
Section: Related Workmentioning
confidence: 99%
“…We argue that understanding the Web hosting landscape is important for a number of reasons. These range from allowing us to assess how critical certain hosting infrastructures are and to estimate the impact that a network attack could have on the Web [8,17,24], to being able to determine who is responsible when incidents (e.g., malware hosting) occur [26]. Despite the importance of the problem, the research community lacks scalable methods to map the hosting landscape.…”
mentioning
confidence: 99%